OPTIMIZATION OF ANNEALING TEMPERATURE AND PRIMER CONCENTRATION OF CYTOCHROME B (CYT B) GENE FOR PIG DNA DETECTION WITH REAL-TIME PCR METHOD - Novia Azahra Fatoni; Ai Djuminar; Acep Tantan Hardiana; Fusvita Merdekawati (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: One company in Indonesia has developed a pig DNA detection kit by designing primers with the real-time Polymerase Chain Reaction (PCR) method using the cytochrome b (cyt b) gene. It is necessary to optimize the PCR process to optimize pig DNA detection, including annealing temperature and primer concentration, which can increase sensitivity, specificity, and precision. Purpose: This research aims to determine the optimum annealing temperature and primer concentration for the detection of pig DNA using cyt b gene. Method: In this research, the extracted sample isolates were subjected to 12 treatments with 2 repetitions. Optimal data analysis was based on the lowest Cycle Threshold (CT) value in the amplification curve. Result: Out of a total of 24 samples, an increase in the CT value was observed at annealing temperatures of 57 °C, 59 °C, and 60 °C compared to 58 °C, across various primer concentrations. The primer concentrations with the lowest CT values were successively found to be 0.4 μM, 0.3 μM, and 0.2 μM. Conclusion: The results of the research that has been conducted indicate that the optimal annealing temperature for detecting pig DNA using the cyt b gene in this research is 58 °C, and the optimal concentrations of forward and reverse primers are 0.4 μM.